Pengaruh Gaya Kepemimpinan, Stres Kerja & Motivasi Kerja Terhadap Kinerja Personel Polres Luwu Timur - Awaluddin, Awaluddin; Laekkeng, Mursalim; Basalamah, Muhammad Syafii (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of leadership style, job stress, and work motivation on personnel performance at the East Luwu Police. The research questions focus on how these three variables simultaneously and partially influence personnel performance, given the stressful and resource-constrained working conditions within the police force. This study employed a quantitative approach using Structural Equation Modeling (SEM) analysis. Data were collected through questionnaires distributed to 100 personnel selected using purposive sampling from a population of 388. The research instrument drew on relevant theories such as Transformational Leadership Theory, Herzberg's Two-Factor Theory, and Self-Determination Theory. The results of the study indicate that: (1) leadership style has a positive and significant effect on personnel performance, (2) work stress has a negative but significant effect on personnel performance, and (3) work motivation acts as a mediating variable, strengthening the influence of leadership style on performance and mitigating the negative impact of work stress. This study concludes that improving the performance of East Luwu Police personnel can be achieved through strengthening a supportive leadership style and effective work stress management, with work motivation as the key liaison. Keywords: Leadership Style, Work Stress, Work Motivation, Performance, Police.